Orexin type-2 receptor distribution in genetic absence epileptic rats from Strasbourg - Onat, F.; Mutlu, N.; Elmas, M. Acikel; Ozdemir, N. Sevinc; Carcak, N. (WILEY, 2024)
15th European Epilepsy Congress, Rome, ITALY, SEP 07-11, 2024